RHETORICAL STRATEGY FOR DELIVERING ANIES BASWEDAN'S VISION OF SUSTAINABLE DEVELOPMENT: FROM INTERNATIONAL FORUMS TO LOCAL CAMPAIGNS - Ryan, Teuku Ryan Firmansyah; Muttaqin, Khoirul (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2025)
Rhetoric, as the art of persuasive speaking, plays a vital role in political communication, particularly in shaping public image and conveying a political vision to the public. This study aims to analyze the rhetorical strategies employed by Anies Baswedan in articulating his vision of sustainable development, both in international forums and local campaign settings. The analysis focuses on the use of three classical rhetorical elements as defined by Aristotle—ethos (credibility), pathos (emotion), and logos (logic)—and examines public responses to these rhetorical strategies. This research adopts a descriptive qualitative approach, utilizing data collection techniques through observation and document analysis of Anies Baswedan’s speech videos and transcripts shared on social media platforms such as YouTube, TikTok, and Instagram. Public comments were also collected and analyzed as indicators of societal responses to the speeches. The data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing.The findings reveal that Anies Baswedan's rhetorical strategies are predominantly characterized by the use of logos, marked by rational and logical argumentation in addressing sustainable development issues. Ethos is demonstrated through the emphasis on personal experience and achievements, while pathos is employed to evoke emotional resonance, enthusiasm, and social concern among the audience. Public responses to these rhetorical strategies are diverse, ranging from support and appreciation for his method of vision delivery to criticism regarding perceived inconsistencies between rhetoric and actual track record. These findings indicate that the success of political communication depends not only on the strength of rhetorical expression but also on the degree of public trust in the communicator’s integrity.